Corporate Social Responsibility and Earnings Management: Measurement Approach Review - Aliyu Suleiman Kantudu; Ibrahim Aliyu Gololo (Journal of Accounting Research, Organization and Economics, 2020)
Objective – This study examines conceptually corporate social responsibility and earnings management measurement approach review.  It reviews existing measurement approaches used in the empirical studies. Problems that led to lack of standardize measurement approach for both CSR and EM were identified and the solutions to the problems were highlighted. Design/methodology – Explanatory research design was employed in the study to review measurements approach for the earnings management and corporate social responsibility used by previous empirical studies. Results – The review of measurement approach reveals that up to today there is no standardized way to measure CSR and EM as studies normally select the method that suit their purpose. Some of the points of contention among scholars  were lack of consensus on the best and standardized way to measure CSR, subjectivity and bias issue with regards to measurement, myriads of models for EM measurement and the voluntary nature of CSR activities and disclosure way. However, in order to address the contentious issues, this study, therefore recommends that relevant agencies should set up standardize way to measure CSR of different companies, on their part government and authorities concern should find way to standardized CSR reporting, makes CSR activities and disclosure mandatory for companies and separation of measurement approach for financial related business companies and non-financial related business companies should be done.